Cheap Talk and Cherry-Picking: What ClimateBert has to say on Corporate Climate Risk Disclosures - Bingler, Julia Anna; Kraus, Mathias; Leippold, Markus; Webersinke, Nicolas (Finance Research Letters, 2022)
Disclosure of climate-related financial risks greatly helps investors assess companies' preparedness for climate change. Voluntary disclosures such as those based on the recommendations of the Task Force for Climate-related Financial Disclosures (TCFD) are being hailed as an effective measure for better climate risk management. We ask whether this expectation is justified. We do so with the help of a deep neural language model, which we christen ClimateBert. In analyzing the disclosures of TCFD-supporting firms, ClimateBert comes to the sobering conclusion that the firms' TCFD support is mostly cheap talk and that firms cherry-pick to report primarily non-material climate risk information.<br
Keywords: Climate-risk disclosure; Voluntary reporting; TCFD recommendations; Natural language processing